STRATEGI OPEN-TRANSMITING DALAM MENINGKATKAN AKUNTABILITAS SEKOLAH DAN KEPERCAYAAN MASYARAKAT TERHADAP SD 1 UNDAAN KIDUL KUDUS - Kris Hardi Wiyono (Universitas Muria Kudus, 2019)
Improper communication between school and parent negatively impact the level of school accountability and community trusts. Therefore it is necessary to find the root of the problem and its solution. To solve the problem, the writer in the capacity as principal and management control holder in SD 1 Undaan Kidul Kudus use maximal service strategy that is open-transmitting. The term open-transmitting is an acronym of the open-transparant word - meeting - home visiting which is the original and pure thought of the author's own creativity. The execution of the strategy is in the form of activities related to the principle of openness, activities related to transparency (transparant), organizing meetings and conducting home visiting (home visits / gatherings). The results achieved are increased school accountability, awakening a sense of kinship and togetherness between schools, school committees, parents and the community, awakening a sense of belonging to the parents and community, increasing trust, awareness and community participation in the provision of education in elementary 1 of Kidul Kudus, increasing of support from village government toward progress of SD 1 Undaan Kidul Kudus and increasing positive image of excellence and uniqueness owned by SD 1 Undaan Kidul Kudus